The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3168/jds.2009-3025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum dietary calcium level on calcium and magnesium metabolism in periparturient dairy cows

Abstract: The aim of this study was to investigate the effects of dietary Ca level (4.9, 9.3, and 13.6 g/kg of DM) on Ca and Mg homeostasis in dairy cows around parturition. Cows of the Swedish Red breed (n = 29) with no previous veterinary treatment for milk fever were divided into 3 groups, and each group was fed one of the different diets during the last 15 to 32 d of gestation. Calcium was added as ground limestone, and the Mg concentration was 1.8 g/kg of DM in all diets. After calving the cows were fed similar die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
5
23
0
7
Order By: Relevance
“…Plasma concentrations of Mg were lower in the 2 d after parturition for cows fed lower prepartum DCAD, consistent with other studies that have measured blood mineral responses shortly after parturition (Green et al, 1981;Kronqvist et al, 2011). Administration of exogenous PTH has been shown to decrease urinary Mg excretion, likely due to an increased renal threshold for Mg clearance by the kidneys induced by PTH.…”
supporting
confidence: 82%
“…Plasma concentrations of Mg were lower in the 2 d after parturition for cows fed lower prepartum DCAD, consistent with other studies that have measured blood mineral responses shortly after parturition (Green et al, 1981;Kronqvist et al, 2011). Administration of exogenous PTH has been shown to decrease urinary Mg excretion, likely due to an increased renal threshold for Mg clearance by the kidneys induced by PTH.…”
supporting
confidence: 82%
“…Minerals present in organisms in large amounts are calcium, phosphorus, magnesium, sodium, potassium, chloride and sulfur. In the specific case of calcium, several studies have detected a correlation between low circulating magnesium concentrations and low circulating calcium concentrations in humans (Classen et al, 1986;Paunier, 1992), mice (Zimmermann et al, 2000) and dairy cows (Kronqvist et al, 2011 and. Low magnesium concentrations have been shown to reduce the secretion of PTH (Suh et al, 1973), as well as decrease tissue responsiveness to PTH (Reddy et al, 1973;Rude, 1998).…”
Section: Mineral Balancementioning
confidence: 99%
“…This is in agreement with Thilsing- Hansen et al (2002), who concluded that Ca intake had to be decreased to less than 20 g/day to decrease the incidence of milk fever. In addition, differences in Ca intake have been found to have no effect on the incidence of milk fever or subclinical hypocalcaemia in experimental studies when the minimum level exceeds 20 g/day (Goff and Horst, 1997;Kamiya et al, 2005;Kronqvist et al, 2011). Curtis et al (1984) found no effect of dietary Ca in commercial herds on the incidence of milk fever, although they concluded that all cows in their study were fed well above the recommendations.…”
Section: Discussionmentioning
confidence: 98%
“…However, more than 80% of the present herds that belonged to the lowest third in Mg intake received Mg at rates above the current Nordic recommendation (Nielsen and Volden, 2011), and the NRC (NRC, 2001) recommendations and the former Swedish recommendations (Spö rndly, 2003) recommend even lower levels of Mg. There are also other indications that the current recommendation is too low (Kronqvist et al, 2011). For example, Goff (2008) suggests more than twice the dietary Mg level stated in Nordic recommendations to ensure adequate Mg absorption during the dry period.…”
Section: Discussionmentioning
confidence: 99%